Hudson Bay; or, Everyday life in the wilds of North America, during six years' residence in the territories of the Hon. Hudson Bay Company. - Ballantyne, R. M. (Robert Michael), 1825-1894. (London, New York, T. Nelson and Sons, 1879)
First edition, Edinburgh, 1848. Added t.-p., with vignette. Mode of access: Internet.